PENERAPAN STRATEGI QUICK ON THE DRAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI KELAS X MIA1 SMA AL-FALAH KOTA JAMBI - Setianto, Sydik Dwi; Hendri, Menza; Darmaji, Darmaji (EduFisika: Jurnal Pendidikan Fisika, 2020)
This study aims to increase student activity and learning outcomes. This research method is classroom action research. This research is a classroom action research which consists of three cycles. The subjects of this study were students of class X MIA1 SMA Al-Falah. The research instrument used the observation sheet and test. The results of observations were analyzed descriptively qualitatively, while the test results were analyzed using descriptive statistics. The increase in student activity can be seen from the average percentage of student activity in the first cycle is 50.20%, an increase in the second cycle to 67.70%, and an increase in the third cycle to 88.85%. While the learning outcomes of the first cycle 67.50 increased in the second cycle to 72.50 and then increased in the third cycle to 77.50. The results of this study indicate an increase in activity and student learning outcomes of physics in each cycle. From the results of the study it can be concluded that the application of active learning strategies type quick on the draw can increase activity and physics learning outcomes in the material quantities and units in class X MIA1 SMA Al-Falah Jambi City.